Effect of Insurance Status on Mortality in Adults With Sarcoma of the Extremities and Pelvis: A SEER-Medicare Study. Issue 1 (1st January 2023) - Jang, Eugene S.; Hammoor, Bradley; Enneking, F. Kayser; Chan, Chung Ming; Spiguel, Andre R.; Gibbs, C. Parker; Scarborough, Mark T.; Tyler, Wakenda K.
Abstract : Introduction: Previous studies have highlighted the association between insurance status and poor outcomes after surgical treatment of sarcomas in the United States. 1 - 3 It is unclear how much of this disparity is mediated by confounding factors such as medical comorbidities and socioeconomic status and how much can be explained by barriers to care caused by insurance status. Methods: Surveillance, Epidemiology, and End Results-Medicare linkage data were procured for 7, 056 patients undergoing treatment for bone and soft-tissue sarcomas in the extremities diagnosed between 2006 and 2013. A Cox proportional hazards model was used to assess the relative contributions of insurance status, medical comorbidities, tumor factors, treatment characteristics, and other demographic factors (race, household income, education level, and urban/rural status) to overall survival. Results: Patients with Medicaid insurance had a 28% higher mortality rate over the period studied, compared with patients with private insurance (hazard ratio, 1.28; 95% confidence interval, 1.03 to 1.60, P = 0.026), even when accounting for all other confounding variables. The 28% higher mortality rate associated with having Medicaid insurance was equivalent to being approximately 10 years older at the time of diagnosis or having a Charlson comorbidity index of 4 rather than zero (hazard ratio, 1.27). Discussion: Insurance status is an independent predictor of mortality from sarcoma, with 28% higher mortality in those with pre-expansion Medicaid. 4, 5 This association between insurance status and higher mortality held true even when accounting for numerous other confounding factors. Additional study is necessary into the mechanism for this healthcare disparity for the uninsured and underinsured, as well as strategies to resolve this inequality.